Exploring Topics and Genres in Storytime Books: A Text Mining Approach - Joo, Soohyung; Ingram, Erin; Cahill, Maria (Evidence Based Library and Information Practice, 2021)
Objective – While storytime programs for preschool children are offered in nearly all public libraries in the United States, little is known about the books librarians use in these programs. This study employed text analysis to explore topics and genres of books recommended for public library storytime programs.Methods – In the study, the researchers randomly selected 429 children books recommended for preschool storytime programs. Two corpuses of text were extracted from the titles, abstracts, and subject terms from bibliographic data. Multiple text mining methods were employed to investigate the content of the selected books, including term frequency, bi-gram analysis, topic modeling, and sentiment analysis.Results – The findings revealed popular topics in storytime books, including animals/creatures, color, alphabet, nature, movements, families, friends, and others. The analysis of bibliographic data described various genres and formats of storytime books, such as juvenile fiction, rhymes, board books, pictorial work, poetry, folklore, and nonfiction. Sentiment analysis results reveal that storytime books included a variety of words representing various dimensions of sentiment.Conclusion – The findings suggested that books recommended for storytime programs are centered around topics of interest to children that also support school readiness. In addition to selecting fictionalized stories that will support children in developing the academic concepts and socio-emotional skills necessary for later success, librarians should also be mindful of integrating informational texts into storytime programs.